Anyone listening? No evidence for eavesdropping on male singing interactions in the great tit, Parus major. (June 2021) - Bircher, Nina; van Oers, Kees; Naguib, Marc
Abstract : Observing interactions between others can provide important information to individuals. Male songbirds often engage in singing contests where they vary the type and timing of signals and provide eavesdropping individuals with information about their competitiveness. How this information is used and its effect on subsequent spatial behaviour and reproductive decisions of eavesdroppers is not well understood. Here we tested whether great tits use information gathered by eavesdropping on male singing interactions to assess rivals and (potential) mates. We used interactive playback experiments to engage territorial males in song contests with either a more (song overlapping and more persistent singing) or less challenging (song alternating and less persistent singing) intruder. We followed male and female movements by automated radiotracking, determined paternity using microsatellite analysis and maternal investment by quantifying egg weights and provisioning behaviour. We expected that mates of males exposed to the challenging treatment would subsequently foray more often off territory to assess other males and potential extrapair mates and invest less in their broods. Moreover, we expected that neighbours would adjust their foraying behaviour according to information gained by eavesdropping. Females, however, did not alter their foraying behaviour or brood investment and neither female nor male neighbours changed their visiting behaviour to playback territories. Our results provide no evidence that females used information gathered by eavesdropping on asymmetric song interactions in reproductive decisions or that song interactions affected movements across territories in the neighbourhood. Overlapping or singing for a longer time on an intruded upon territory may not always be perceived as a higher level of threat, and reproductive decisions and assessment of familiar individuals are likely to be based on multiple sources of information rather than on a single interaction. Highlights: First study to radiotrack mate and neighbour responses to male birdsong playback. Female reproductive decisions were not affected by a male singing interaction. Females did not foray more into neighbouring territories after territorial challenge. Forays by neighbours did not change after playback. Female mate assessment appears robust against short-term information changes.